Sikap Bidan Terhadap Keberhasilan Inisiasi Menyusu Dini (IMD) - Yola Fadelia; Erna Rahma Yani; Sumy Dwi Antono (Malang Journal of Midwifery (MAJORY), 2021)
Early initiation of Breastfeeding (IMD) is the process of the baby to suckle soon after being born or the baby left looking for her mother's nipples. One of the factors that play an important role in the success of the implementation of the IMD is to support the health workers or that can be realized from the attitude and behavior of health workers. According to the Health Profile of Indonesia year 2017 to 2018 achievement of the IMD in the newborn decreased from 73,06% be 71,17%. The purpose of this study is to determine a relationship of the attitude of the midwife towards the success of the IMD in the Aura Syifa Hospital Kediri Regency. Type of research used Cross Sectional approach. The population in this study was all midwives on duty in the room of maternity as many as 17 people. The sample used in this study consisted of 17 respondents with a Total sampling technique. Data collection using questionnaires and data collection tools in the success of the IMD using the observation sheet. Data analysis using statistical test Fishers Exact. The results of statistical tests using a test with level ? = 0.05 where ? value = 0,015. From the results of the count 0.015 < 0.05 then H0 is rejected, H1 is accepted so it can be concluded that There is a relationship of the attitude of the midwife towards the success of the IMD in the Aura Syifa Hospital Kediri Regency. For the next expected to the midwife to apply the IMD is better again with regard to the condition of the baby and the mother. Keywords: Midwife’s Attitudes, Early Initiation of Breastfeeding.